2004
DOI: 10.1088/0953-4075/37/18/003
|View full text |Cite
|
Sign up to set email alerts
|

Photofragmentation study of core-excited NO

Abstract: The production of anionic and cationic fragments of NO has been measured after photoexcitation in the vicinity of the nitrogen 1s threshold. The partial ion yield for the anionic fragment O − , in conjunction with the partial cation yields, can clearly distinguish the shape resonances from doubly excited states. On the N 1s → π * resonances, which are composed of the three intermediate states 2 , 2 − and 2 + in the order of increasing photon energy, the intensity ratios for the NO ++ , O + and O ++ fragments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
(53 reference statements)
0
30
0
Order By: Relevance
“…1͑c͒ the sum of the two partial Auger spectra, both for the experimental and theoretical results, is compared with the noncoincidence one measured simultaneously. 31 Thus it is not unlikely that decay to N 2 O + may occur. 22 The theoretical simulation reproduces the summed coincidence experiment very well, both in the shape and the relative intensity of the three main features.…”
Section: Resultsmentioning
confidence: 99%
“…1͑c͒ the sum of the two partial Auger spectra, both for the experimental and theoretical results, is compared with the noncoincidence one measured simultaneously. 31 Thus it is not unlikely that decay to N 2 O + may occur. 22 The theoretical simulation reproduces the summed coincidence experiment very well, both in the shape and the relative intensity of the three main features.…”
Section: Resultsmentioning
confidence: 99%
“…SF 6 , SiF 4 ), and at variance with many smaller molecules (e.g. CO, CO 2 , NO, N 2 O) for which the shape resonance is almost completely suppressed [24,29,30,32], [70]- [72]. Many studies showed that multiple scattering of photoelectrons by neighboring atoms is essential for the interpretation of shape resonance features in x-ray absorption spectra, particularly for large molecules and the solid phase [73]- [76].…”
Section: Resultsmentioning
confidence: 99%
“…While it had been presumed that negative ion is emitted from singly charged ion states produced by resonant Auger decay of core-excited states, the direct evidence to the mechanism was recently offered by a negative-positive ion coincidence measurement [179]. Lindle and co-workers proved that the observation of negative fragment ions can be a probe to postcollision interaction [180] and to doubly excited states embedded in inner-shell ionization continua [181].…”
Section: Negative Ion Detectionmentioning
confidence: 99%